Amplitude analysis and branching fraction measurement of B+ → D∗−D+ s π+ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
The decays of the B+ meson to the final state D∗−D+ s π+ are studied in protonproton collision data collected with the LHCb detector at centre-of-mass energies of 7, 8, and 13TeV, corresponding to a total integrated luminosity of 9 fb−1. The ratio of branching fractions of the B+ → D∗−D+ s π+ and B0 → D∗−D+ s decays is measured to be 0.173 ± 0.006 ± 0.010, where the first uncertainty is statistical and the second is systematic. Using partially reconstructed D∗+ s → D+ s γ and D+ s π0 decays, the ratio of branching fractions between the B+ → D∗−D∗+ s π+ and B+ → D∗−D+ s π+ decays is determined as 1.31±0.07±0.14. An amplitude analysis of the B+ → D∗−D+ s π+ decay is performed for the first time, revealing dominant contributions from known excited charm resonances decaying to the D∗−π+ final state. No significant evidence of exotic contributions in the D+ s π+ or D∗−D+ s channels is found. The fit fraction of the scalar state T∗ c¯s0(2900)++ observed in the B+ → D−D+ s π+ decay is determined to be less than 2.3% at a 90% confidence level.